2008
DOI: 10.1097/brs.0b013e3181761003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Lentiviral and Adenoviral Gene Therapy for Spinal Fusion in Rats

Abstract: BMP-2-producing RBMCs developed using lentiviral gene transfer induced more abundant bone within the fusion mass than the RBMCs transduced via adenoviral gene transfer and recombinant protein therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 28 publications
0
37
1
Order By: Relevance
“…Because previous studies reported highly consistent results for ACS 18,25 in this model, only four animals were included in this negative control group. As in previous similar studies, 18,21,22 for TrioMatrix 1 , Grafton 1 , and DBX 1 , 0.3 cm 3 were implanted on each side for a total volume of 0.6 cm 3 per animal.…”
Section: Study Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because previous studies reported highly consistent results for ACS 18,25 in this model, only four animals were included in this negative control group. As in previous similar studies, 18,21,22 for TrioMatrix 1 , Grafton 1 , and DBX 1 , 0.3 cm 3 were implanted on each side for a total volume of 0.6 cm 3 per animal.…”
Section: Study Groupsmentioning
confidence: 99%
“…Histologic Analysis Utilizing a previously described protocol, 25 four harvested spines underwent histologic analysis, performed in the Northwestern University Pathology Core Facility. After detachment of surrounding soft tissue, spine specimens were fixed in 10% neutral-buffered formalin, decalcified in HCl/ EDTA, and embedded in paraffin.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Given that the bone regeneration is a long-term process, lentiviral vectors may be a more useful tool for the repair of various bone defects, especially large bone defects or those within a compromised biological environment [22]. Miyazaki et al [23] have found that lentiviralmediated BMP2 gene transfer could achieve more abundant bone formation in a rat spinal fusion model compared with adenoviral-mediated gene transfer. The duration of gene expression is also a factor related to the quality of bone formed during gene therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of gene therapy applications with lentiviral vectors have been ex vivo, because of this vector's association with the human immunodeficiency virus. Repair of bone defects treated with syngeneic rat bone marrow cells transduced with lentiviral vectors expressing BMPs have been compared to repair with cells transduced with adenoviral vectors (Hsu, et al, 2007;Miyazaki, et al, 2008;Virk, et al, 2008). Prolonged therapeutic BMP expression provided with the lentiviral vector in a critical sized femoral defect model provided superior repair associated with regional gene therapy than that observed with adenoviral vectors (Hsu et al, 2007;Virk, et al, 2008).…”
Section: Viral Vectorsmentioning
confidence: 99%
“…In a spinal fusion model, MSCs expressing BMP after lentiviral transfer induced more abundant bone within the spinal fusion mass then cells transduced with adenovirus. Cells transduced with lentivirus or adenovirus expressing BMP both outperformed recombinant BMP protein therapy (Miyazaki, et al, 2008). Both the MLV-based and the lentiviral-based retroviral vectors have displayed characteristic preferences for integration sites, with the MLV-based vector integration associated with transcription start regions and lentiviral vector integration associated with sites of active gene transcription (Mitchell et al, 2004).…”
Section: Viral Vectorsmentioning
confidence: 99%